Patterns of Several Heavy Metals Accumulation across Age and Gender Group - Tawir, Duha Yahya; Hussein, Haider Mashkoor (American Journal of Biology and Natural Sciences, 2025)
Some metals are considered non-essential for biological processes, such as zinc (Zn), the metal lead (Pb), the metal mercury (Hg), the arsenic (As), the nickel (Ni), and cadmium (Cd)., Conversely, elements such as molybdenum, manganese, copper, iron, and zinc are vital in minute amounts. Any hazardous metal can be classified as a heavy metal, regardless of its atomic weight or density. Seventy-five samples from both gender were included in the present study with age range (15_70 years). 50 patients with blood diseases were selected from Teaching Al-Diwaniyah Hospital; and 25 participent apparently healthy control group. Heavy metals parameters measurement was performed on blood serum by use (Atomic absorption spectrophotometer), model Buck Scientific - 210VGP Atomic Absorption Spectrophotometer. The blood serum, were digestion to examine the heavy elements of the total study sample (treatment and control).The results showed that females represented 52% of the sample, while males accounted for 48%, indicating a balanced gender distribution. The most represented age group was 26–37 years (22.67%), highlighting a focus on generally active age groups. Data analysis revealed statistically significant effects of gender and age on the amounts of certain minerals in bloodstreams, like lead, also known as Pb, as well as aluminium (Al),with p-values < 0.05 indicating statistical significance. For instance, lead levels were seen to be elevated in males relative to females. This highlights the need to consider environmental factors that affect health. This study seeks to examine the influence of gender, age, on the concentration of metals in the blood.